2020
DOI: 10.1007/s00268-020-05531-0
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐Term and Long‐Term Impact of Permanent Hypoparathyroidism After Total Thyroidectomy

Abstract: Background Permanent hypoparathyroidism (PH) is the most frequent long-term complication after total thyroidectomy. PH is related to many short-term and long-term complications, including clinical manifestations of hypocalcemia, hypercalcemia due to overtreatment, hyperphosphatemia, gastrointestinal, neuropsychiatric symptoms, decrease in renal function and infectious complications. The aim of this study was to identify the most frequent effects of PH and its associated risk factors. Methods We performed a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Retrospective claims database studies reported that patients with hypoparathyroidism were at increased risk of developing CKD, nephrolithiasis, nephrocalcinosis and decline in eGFR compared with individuals without hypoparathyroidism 6,8,9 . Another retrospective analysis that specifically included patients with postsurgical chronic hypoparathyroidism and who were treated with conventional therapy demonstrated that 26% of patients had a decline in eGFR of ≥25% and 10% developed CKD within 1 year after surgery 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective claims database studies reported that patients with hypoparathyroidism were at increased risk of developing CKD, nephrolithiasis, nephrocalcinosis and decline in eGFR compared with individuals without hypoparathyroidism 6,8,9 . Another retrospective analysis that specifically included patients with postsurgical chronic hypoparathyroidism and who were treated with conventional therapy demonstrated that 26% of patients had a decline in eGFR of ≥25% and 10% developed CKD within 1 year after surgery 18 …”
Section: Discussionmentioning
confidence: 99%
“…6,8,9 Another retrospective analysis that specifically included patients with postsurgical chronic hypoparathyroidism and who were treated with conventional therapy demonstrated that 26% of patients had a decline in eGFR of ≥25% and 10% developed CKD within 1 year after surgery. 18 We hypothesized that, based on the stabilization of serum calcium levels, reduction in calcium excretion by the kidneys and stable eGFR observed in long-term trials of rhPTH(1-84), rhPTH(1-84) replacement therapy may offer a renoprotective effect. 15,16 Indeed, the results of the current study demonstrated that the treatment of patients with chronic hypoparathyroidism with a regimen that included rhPTH America and five European countries of patients with chronic hypoparathyroidism receiving conventional therapy reported that patients whose disease was not adequately controlled had a higher proportion of renal complications and CKD, and had higher hypoparathyroidism-related healthcare resource utilization, compared with patients whose disease was adequately controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting reports exist regarding the correlation between IP and HYP. 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Many authors suggest that a surgeon must try to find and preserve at least three PGs by any means. Among them, Ponce de Leon-Ballesteros et al.…”
Section: Discussionmentioning
confidence: 99%
“…After thyroidectomy, 19%–38% and 0%–3% of patients presented with transient and permanent hypoparathyroidism, respectively 27 . Permanent hypoparathyroidism is associated with multiple complications, including renal function impairment, gastrointestinal and neuropsychiatric problems, and infections 28 . Second, TT is also associated with a greater risk of recurrent laryngeal nerve injury.…”
Section: Discussionmentioning
confidence: 99%